Use of chloroplast DNA polymorphisms to define maternal provenance regions for the white oaks of the Iberian Peninsula - Herran, A.; Espinel, S.; Goikoetxea, P. G. (Forest Systems, 1999)
We present here the results obtained after the study of 156 oak populations collected along the Iberian Peninsula. Six oak species were present in the sample: Quercus canariensis, Q. faginea, Q. humilis, Q. pyrenaica, Q. robur and Q. petraea. Five trees from each population were analyzed with four cpDNA specific pairs of primers that allowed the distinction of 13 haplotypes. In populations with several species, all of them shared the same haplotype, and none of the common haplotypes was restricted to a single species. Analysis of molecular variance in the data revealed a strong genetic structure. Maternal provenance regions were defined that maximize the among groups variance and minimize the among populations/within groups variance. The distribution of the haplotypes suggests the existence of several distinct refugia, not restricted to the South of the Peninsula.